Protective Behavioural Mechanisms Against Cannabis Use Among Adolescents in Cannabis-Growing Settings of South Africa: Insights Into Adolescent Cannabis Use Prevention. (9th December 2022) - Manu, Emmanuel; Douglas, Mbuyiselo; Ntsaba, Mohlomi Jafta; Makaula, Bekwa; Tarkang, Elvis Enowbeyang
We aimed to explore the behavioural protective mechanisms against cannabis use among adolescents living in South African illicit cannabis-growing communities, based on the Self Determination Theory (SDT). Exploratory qualitative design techniques were followed in conducting the study. The snowball sampling technique was used to recruit thirty (30) non-cannabis smoking adolescents from 2 purposively selected communities and grouped into 4 focus groups and interviewed. A semi-structured focus group interview guide was used to moderate the discussions. Data were analysed inductively, using the ATLAS. ti software. Nine behavioural coping mechanisms, grouped under intrinsic and extrinsic protective behavioural mechanisms, protected participants from using cannabis. Intrinsically, participants' determination not to engage in bad behaviours, focus on their academic work during their free periods, their non-financial dependence on cannabis-using peers, self-preservation to ensure good marriages, and religious beliefs on substance abuse motivated them to not use cannabis. On the other hand, the concept of Ukuphoxa (preservation of family dignity), fear of arrest, fear of being tagged a social deviant, and the fear of contracting illnesses such as lung cancer served as protective behavioural mechanisms against cannabis use. Health promotion and education programmes for adolescents on non-cannabis use in communities where illicit cannabis abounds must identify and draw on contextual intrinsic and extrinsic motivations that ensure non-cannabis use.